Diversity of Intestinal Macrophages in Inflammatory Bowel Diseases - Kühl, Anja A.; Erben, Ulrike; Kredel, Lea I.; Siegmund, Britta (Frontiers in Immunology, 2015)
Macrophages as innate immune cells and fast responders to antigens play a central role in protecting the body from the luminal content at a huge interface. Chronic inflammation in inflammatory bowel diseases massively alters the number and the subset diversity of intestinal macrophages. We here address the diversity within the human intestinal macrophage compartment at the level of similarities and differences between homeostasis and chronic intestinal inflammation as well as between UC and CD including the potential role of macrophage subsets for intestinal fibrosis. Hallmark of macrophages is their enormous plasticity i.e. their capacity to integrate signals from their environment thereby changing their phenotype and functions. Tissue-resident macrophages located directly beneath the surface epithelium in gut homeostasis are mostly tolerogenic. The total number of macrophages increases with luminal contents entering the mucosa through a broken intestinal barrier in ulcerative colitis as well as in Crohn’s disease. Although not fully understood, the resulting mixtures of tissue-resident and tissue-infiltrating macrophages in both entities are diverse with respect to their phenotypes and their distribution. Macrophages in ulcerative colitis mainly act within the intestinal mucosa. In Crohn’s disease, macrophages can also be found in the muscularis and the mesenteric fat tissue compartment. Taken together, the present knowledge on human intestinal macrophages so far provides a good starting point to dig deeper into the similarities and differences of functional subsets and to finally use their phenotypical diversity as markers for complex local milieus in health and disease